AB033. Assessing the appropriateness of pharmacological prescriptions for COPD to clinical guidelines: EPOCONSUL study - Alcázar, Bernardino (J Thorac Dis, 2016)
BACKGROUND: Adherence to clinical practice guidelines is far from optimal for most of the chronic diseases. Spain has implemented a phenotype based chronic obstructive pulmonary disease (COPD) guideline and there is scarce data about the follow-up of this guideline. The aim of this study is to evaluate the suitability of the pharmacological treatment for COPD to the Spanish Guidelines (GesEPOC) recommendations in patients with COPD recruited at respiratory clinics around Spain. METHODS: EPOCONSUL study is a observational, multicentre, cross-sectional study aimed to audit clinical histories from stable COPD patients attended at respiratory offices. Patients were recruited prospectively from 62 centres around Spain along June 2014 to June 2015. RESULTS: The EPOCONSUL study audited 4,501 medical histories from patients with COPD. Characteristics of study population showed 86.0% males, with a mean age (± SD) of 69.77±9.79 years. In 76.9% of the cases patients were attended at general respiratory offices. Baseline FEV1 values were 52.3%±18.4% of predicted. A COPD diagnosis using GesEPOC guidelines was performed in 2,087 patients (46.3%). The most preferred treatment option was the association of ICS/LABA in fixed-dose combination and LAMA, that was used in 2,450 patients of the whole sample. Among patients with a diagnosis of COPD according to GesEPOC guidelines, the preferred form of treatment was: non-exacerbators (LAMA/LABA 37.8%, LAMA/LABA/ICS 36.6%, LAMA 15.9% and LABA/ICS 4.9%), Asthma-COPD overlap syndrome (LAMA/LABA/ICS 61.9%, LABA/ICS 21.9%, LAMA/LABA 10.3% and LAMA 2.9%), frequent exacerbator with emphysema (LAMA/LABA/ICS 69.2%, LAMA/LABA 18.3%, LABA/ICS 6.4%, and LAMA 3.2%) and finally frequent exacerbator with chronic bronchitis (LAMA/LABA/ICS 77.0%, LAMA/LABA 14.0%, LABA/ICS 5.9% and LAMA 1.1%). CONCLUSIONS: According to EPOCONSUL study data, the most used pharmacological option for COPD in Spain is triple therapy, which is prescribed in more than half of the patients. There are many appropriate prescriptions in patients with frequent exacerbations but not so in patients without frequent exacerbations.